Study guides

☆☆

Q: What is the answer to the square root of 4x2 times the square root of 36x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

In real numbers there is no square root of -4x2 However, when using complex numbers where √-1 = i, then: √-4x2 = 2xi If you were asking, for example, with regard to the difference of two squares, eg y2 - 4x2, then you are actually finding the square root of 4x2 which is 2x, giving: y2 - 4x2 = (y + 2x)(y - 2x)

b. -4x2+20 = 4x2 = 4-20x2 = -16x = -4Note that -42 = -16 but (-4)2 in brackets = 16

Using the quadratic equation formula to find the answer: If: (2x -9)(2x-9) = 0 Then: x = 9/2 and also x = 9/2 (they both have equal roots) Check that your answer is correct by multiplying out the brackets which should bring you back to 4x2-36x+81.

Only if the value of c is 9 because:- 4x2+12x+9 = (2x+3)(2x+3)

The answer depends on the units used for the length of the sides. If they are millimetres, the answer is 0.000004x2 square metres if they are centimetres, the answer is 0.0004x2 square metres if they are metres, the answer is 4x2 square metres if they are kilometres, the answer is 4,000,000x2 square metres.

Related questions

4x2-36x+81 (2x-9)(2x-9)

81.

In real numbers there is no square root of -4x2 However, when using complex numbers where √-1 = i, then: √-4x2 = 2xi If you were asking, for example, with regard to the difference of two squares, eg y2 - 4x2, then you are actually finding the square root of 4x2 which is 2x, giving: y2 - 4x2 = (y + 2x)(y - 2x)

4x2 - 36x + 81 = 4x2 - 18x - 18x +81 = 2x(2x - 9) - 9(2x - 9) = (2x - 9)2

The expression is likely 4x2 - 36x +81 which is the same as (2x - 9)(2x - 9) or (2x - 9)2

(2x - 9)(2x - 9)

x = square root of 3.

Only if the term under the radical (square root sign) can be simplified to a rational expression. For example, âˆš(4x2).

10x2 - 64 = 36x + 6x2Subtract 6x2 from both sides:4x2 - 64 = 36xSubtract 36x from both sides:4x2 - 36x - 64 = 0Divide everything by 4:x2 - 9x - 16 = 0Use the quadratic formula:x = (9Â±âˆš(92-4(-16)))/(2)x = (9-âˆš(145))/2 or x = (9+âˆš(145))/2

(2x - i)(2x + i)where i is the square root of negative 1.x = 0.5i, -0.5i

Sqrt(24x4)/Sqrt(3x) = Sqrt(24x4/3x) = Sqrt(8x3) = Sqrt(4x2*2x) = 2x*sqrt(2x)

b. -4x2+20 = 4x2 = 4-20x2 = -16x = -4Note that -42 = -16 but (-4)2 in brackets = 16

People also asked